PENGARUH TATA KELOLA PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Sektor Industri Dasar dan Kimia yang terdaftar di Bursa Efek Indonesia Periode 2014-2018) - Eka Aprillian; Dini Wahjoe Hapsari (Universitas Pamulang, 2020)
Earnings management is an action that is often done by companies, it aims to enhance your financial statements with the intention that investors are much more interested in investing, to get bonuses and get ease in getting loans. This can be detrimental to some stakeholders who use financial statements as a source of information in making decisions. This study aims to determine the effect simultaneously and partially between managerial ownership, independent commissioners, audit committees, and leverage on earnings management in the basic industrial and chemical sectors for the 2014-2018 period. The method used in this research is a quantitative method. This type of research in this research is descriptive. The sampling technique in this study used a purposive sampling technique using 11 company samples over a period of five years to obtain 55 sample units. This research uses a panel data regression analysis method using the Eviews 9 software. The results of this study indicate that managerial ownership variables, independent commissioners, audit committees, and leverage simultaneously influence earnings management. While partially the audit committee variable has a negative effect on earnings management, managerial ownership and leverage have a positive effect on earnings management. Whereas independent commissioners have no effect on earnings management.